Lemna minor aqueous extract as a natural ingredient incorporated in poly (vinyl alcohol)-based films for active food packaging systems. (June 2022) - Luzi, Francesca; Del Buono, Daniele; Orfei, Benedetta; Moretti, Chiaraluce; Buonaurio, Roberto; Torre, Luigi; Puglia, Debora
Abstract: An aqueous extract of Lemna minor (LE – 0.5%, dry weight/volume), a wild spontaneous aquatic species, was used as an active agent in poly (vinyl alcohol) (PVA) films at the concentrations of 1, 5, 10, 20 wt%, realized through the solvent casting process. This species was selected after determining a high total phenol content (TPC – 6.7 mg g −1 DW) and antioxidant of its aqueous extract. Transparency, color and morphological studies were considered to define the effect of the LE component on the optical properties of the matrix obtained. In addition, antioxidant, antifungal and antibacterial studies were performed to shed light on the LE effect on the active functional properties of the realized films for multifunctional packaging. The optical characterization of the obtained films revealed that the extract of Lemna minor in PVA films induced some alterations, although its presence determined positive radical scavenging and antimicrobial activity. These results demonstrate the possibility of using these polymeric systems in the food packaging sector. Graphical Abstract: ga1 Highlights: An aqueous extract, obtained from a wild aquatic species, was used as antioxidant ingredient. Lemna extract was combined with PVA to get active food packaging. Lemna extract in PVA based systems acts as light-absorbing. Lemna extract in PVA based formulations induced antimicrobial and antifungal effects.